Terapi Foot Massage terhadap Tekanan Darah pada Pasien Hipertensi di Puskesmas X - Miranda Putri Utami; Teti Hayati; Wilda Fauzia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of foot massage therapy on blood pressure in hypertensive patients at the Kemayoran Community Health Center in Central Jakarta. A pre-experimental, one-group pre-test-post-test design was used in 36 respondents. The results showed that before the intervention, the average systolic blood pressure was 149.78 mmHg, and the diastolic blood pressure was 80.72 mmHg. After the intervention, the average systolic blood pressure decreased to 132.94 mmHg and the diastolic blood pressure to 80.22 mmHg (p < 0.05). In conclusion, foot massage therapy is effective in lowering both systolic and diastolic blood pressure in hypertensive patients and can also be used as a supportive intervention for healthcare services. Keywords: Foot Massage, Hypertension, Blood Pressure